Uncovering secrets of the beauty bone: A comprehensive review of anatomy and regional anesthesia techniques of clavicle surgeries - Kartik Sonawane; Hrudini Dixit; J.Balavenkatasubramanian; Palanichamy Gurumoorthi (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
The clavicle is the most frequently fractured bone in humans. General anesthesia with or without Regional Anesthesia (RA) is most frequently used for clavicle surgeries due to its complex innervation. Many RA techniques, alone or in combination, have been used for clavicle surgeries. These include interscalene block, cervical plexus (superficial and deep) blocks, SCUT (supraclavicular nerve + selective upper trunk) block, and pectoral nerve blocks (PEC I and PEC II). The clavipectoral fascial plane block is also a safe and simple option and replaces most other RA techniques due to its lack of side effects like phrenic nerve palsy or motor block of the upper limb. We present a comprehensive review of anatomy and RA techniques of clavicle surgeries. This review will help readers understand the functional anatomy and nature of clavicle fractures, and apply an algorithmic approach to procedure-specific blocks for complexly innervated structures like clavicle.